Pelaksanaan Tahfiz Al-Qur'an di Pondok Pesantren Nur Huda Senting Boyolali Tahun 2017 - Kustanto, Anwar, Drs. M. Darojat Ariyanto, M.Ag (2017)
This research is conducted to know the implementation of tahf Taḥfīẓ Al-Qur'ān idz Al-Qur'ān in Pondok Pesantren Nur Huda Senting Boyolali and the factors that influence it. This research type is qualitative research, that is research which base its analysis not come from statistical calculation. The data obtained through observation, interviews, and documentation. Data analysis used is descriptive qualitative. The results of this study indicate that the program memorizing the Al-Qur'ān in Pondok Pesantren Nur Huda Senting Boyolali is a flagship program of pesantren, the students selected to follow the program memorizing the Qur'an and scouted for about six years to be able to memorize Al-Qur'ān 30 juz. In the implementation tahfidz Al-Qur'ān there are three stages, namely: preparation, implementation, and guard. The method used is the recitation method, which is memorized to ustadz, because this method is for those who have been able to read the Al-Qur'ān with tartile. Factors affecting the implementation of Taḥfīẓ Al-Qur'ān there are two, namely supporting factors and inhibiting factors. The supporting factors include: choosing an expert teacher, choosing the right manuscripts, choosing friends who can memorize, choose time and place, follow musabaqoh, and determine the number of verses to be memorized. While the inhibiting factors include: a lot of disobedience, impatience, laziness, and despair, weak spirit and desire, intention that is not sincere, unable to read well, unable to manage time, unable to distinguish similar verses, repetition A little, no one guides. Based on this research is expected to increase knowledge insight, especially in the field of Taḥfīẓ Al-Qur'ān and input from all parties who need in the Faculty of Tarbiyah UMS Surakarta.